2015
DOI: 10.1016/j.ijpharm.2015.07.042
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of retinoic acid to LNCap human prostate cancer cells using solid lipid nanoparticles

Abstract: In this study retinoic acid (RTA) loaded solid lipid nanoparticles (SLNs) were optimized by tuning the process parameters (pressure/temperature) and using different lipids to develop nanodispersions with enhanced anticancer activity. The RTA-SLN dispersions were produced by high-pressure homogenization and characterized in terms of particle size, zeta potential, drug entrapment efficiency, stability, transmission electron microscopy (TEM), atomic force microscopy (AFM), X-ray diffraction (XRD) and in vitro dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(22 citation statements)
references
References 33 publications
3
19
0
Order By: Relevance
“…AFM revealed nanoparticles of chitosan containing 2-oxothiazolidine-4-carboxylic acid for ocular delivery to be spherical, of uniform shape and with limited aggregation, supporting SEM investigations [57]. [58]; however, these sizes were smaller than those measured using laser diffraction measurements and this was attributed to sample drying and a slight flattening effect caused by the AFM probe. Interestingly, Cai et al found the mean diameters of polystyrene nanoparticles (for skin penetration) to be significantly less than those obtained from photon correlation spectroscopy (PCS) (36.8 ± 7.3, 56.9 ± 0.7 nm, respectively), although the AFM values were considered to be more accurate due to direct interaction of the materials [59]; SiO2 nanoparticles, however, exhibited no difference in particle diameter when examined by AFM and PCS and this was attributed to variations in surface charge.…”
Section: Imaging and Particle Sizingsupporting
confidence: 52%
“…AFM revealed nanoparticles of chitosan containing 2-oxothiazolidine-4-carboxylic acid for ocular delivery to be spherical, of uniform shape and with limited aggregation, supporting SEM investigations [57]. [58]; however, these sizes were smaller than those measured using laser diffraction measurements and this was attributed to sample drying and a slight flattening effect caused by the AFM probe. Interestingly, Cai et al found the mean diameters of polystyrene nanoparticles (for skin penetration) to be significantly less than those obtained from photon correlation spectroscopy (PCS) (36.8 ± 7.3, 56.9 ± 0.7 nm, respectively), although the AFM values were considered to be more accurate due to direct interaction of the materials [59]; SiO2 nanoparticles, however, exhibited no difference in particle diameter when examined by AFM and PCS and this was attributed to variations in surface charge.…”
Section: Imaging and Particle Sizingsupporting
confidence: 52%
“…In vitro cell viability studies revealed that most cell lines can tolerate up to 1 mg/mL of lipid doses of drug-free NLCs [146]. Many studies even provided evidence for adequate cellular tolerability for positively charged lipid-based nanocarriers prepared using cationic surfactants such as cetyltrimethylammonium bromide (CTAB).…”
Section: Toxicity and Biocompatibilitymentioning
confidence: 99%
“…We hypothesized that the combination of two therapeutic components will enhance the antitumor efficacy in melanoma malignancies. It is worth noting that ATRA though exhibits the anticancer properties, did not result in any adverse effect in the systemic environment [23]. As the DBZ is hydrophobic in nature, we have designed lipid nanoformulations that can stably incorporate the hydrophobic drugs in the lipid core and ATRA will be loaded as a structural component of the nanoparticles.…”
Section: Preparation and Characterization Of Dbz/atra-loaded Lipid Namentioning
confidence: 99%